Towards a systematization of Palaeohispanic scripts in Unicode: synthesising multiple transcription hypotheses into two consensus encodings (Palaeohispanica. Review about languages and cultures of Ancient Hispania, 2019)
This work is a unified version of two proposals submitted to the Unicode consortium in order to encode the Palaeohispanic scripts. In the first section we briefly present these scripts and we justify the need to create two different standards to encode them: north-eastern Iberian, which will also include the Celtiberian script, and southern Palaeohispanic, which will include the south-eastern Iberian script, the south-western script and the Es-panca abecedary. In section 2 we describe the specific characteristics of the north-eastern Iberian script, the main conventions used to transcribe it and, finally, we propose the selection of meaningful variants to be encoded as the standard script; the criteria to justify this choice are also explicitly ex-pounded in this section. Finally, section 3 is devoted to describing the spe-cific problematics concerning the southern Palaeohispanic scripts, whose decipherment has not yet been fully achieved. Likewise, at the end of this section we propose the set of all meaningful shapes to be encoded as the standard script.
Keywords: Palaeohispanic scripts; Unicode; Iberian; Celtiberian; Southwestern inscriptions; Espanca abecedary